Composite dietary antioxidant intake and osteoporosis likelihood in premenopausal and postmenopausal women: a population-based study in the United States. Issue 5 (20th May 2023) - Zhang, Ruyi; Ni, Zemin; Wei, Muhong; Cui, Yuan; Zhou, Haolong; Di, Dongsheng; Wang, Qi
Abstract : Using data from the National Health and Nutrition Examination Survey, this study found that the combined intake of antioxidant nutrients was negatively associated with osteoporosis likelihood among middle-aged women, especially for postmenopausal women. Abstract: Objective: Osteoporosis is a skeletal disease characterized by low bone mass, reduced bone strength, and increased fracture risk. We aimed to investigate the association between combined dietary antioxidant intake and the likelihood of osteoporosis in premenopausal and postmenopausal women, based on data from the National Health and Nutrition Examination Survey. Methods: Nutrient intake data were obtained using two 24-hour recalls. Composite dietary antioxidant index (CDAI), which refers to the intake amounts of β-carotene, vitamin A, vitamin C, vitamin E, selenium, zinc, copper, and iron, was then constructed. Prevalent osteoporosis was defined according to bone mineral density T scores of ≤ −2.5 and self-reports. Multiple logistic and Poisson regression models were used for association analyses. Results: A total of 3, 418 participants (1, 157 premenopausal and 2, 261 postmenopausal women) 40 years or older were included, 776 (22.70%) of whom had prevalent osteoporosis. In terms of individual nutrients, postmenopausal women in the highest CDAI quartiles for dietary β-carotene, vitamin A, vitamin C, and iron intakes had a low likelihood of osteoporosis. Regarding the CDAI-osteoporosis association, postmenopausal women in the highest quartile were less likely to have osteoporosis (ORQ3 vs Q1, 0.64; 95% CI, 0.43–0.96; ORQ4 vs Q1, 0.56; 95% CI, 0.35–0.89; P for trend = 0.013), after controlling for covariates. Conclusions: CDAI was negatively associated with the likelihood of osteoporosis in postmenopausal women. Our findings suggest that the combined intake of antioxidant nutrients can help reduce the likelihood of osteoporosis in women.